2016
DOI: 10.1093/schbul/sbw061
|View full text |Cite
|
Sign up to set email alerts
|

Differential Time Course of Microstructural White Matter in Patients With Psychotic Disorder and Individuals at Risk: A 3-Year Follow-up Study

Abstract: Background: Although widespread reduced white matter (WM) integrity is a consistent finding in cross-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 61 publications
3
16
0
Order By: Relevance
“…For all LME models, we compared the Akaike Information Criteria between models with a random intercept and random slope or only a random intercept using the Log-likelihood ratio test and chose the most parsimonious model. To control for longitudinal changes in voxel selection of tracts, we included analytic weights to the LME models examining diffusion values, weighing the error variance inversely by the tract size 69 . In all LME models, age, sex and education and their interaction with time were included as covariate if p < 0.10 (using the Wald t-statistic).…”
Section: Methodsmentioning
confidence: 99%
“…For all LME models, we compared the Akaike Information Criteria between models with a random intercept and random slope or only a random intercept using the Log-likelihood ratio test and chose the most parsimonious model. To control for longitudinal changes in voxel selection of tracts, we included analytic weights to the LME models examining diffusion values, weighing the error variance inversely by the tract size 69 . In all LME models, age, sex and education and their interaction with time were included as covariate if p < 0.10 (using the Wald t-statistic).…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] However, there have been conflicting reports in the localization of white matter alterations across previous studies, which may result from small samples, variable illness duration and antipsychotic and other drug treatment history. [5][6][7][8][9] Another potential reason for inconsistent findings in diffusion tensor imaging (DTI) studies of white matter pathways is that widespread and subtle pathology across the brain might be imperfectly detected by traditional regional or voxel-based analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, Karlsgodt et al 17 and Carletti et al 20 reported negative differences in the FA values in both ARMS-NP and ARMS-P patients at baseline. Domen et al 22 followed the siblings of patients with schizophrenia for 3 years and showed that the whole brain mean FA values of the siblings were smaller than those of HC at all the time-points.…”
mentioning
confidence: 99%